The SCO and the problems of regional security in Central Asia - Akatayeva, А. А. (International relations and international law Journal, 2016)
It is made an attempt to explain and analyze in brief the SCO activities in the sphere of promoting regional security. The paper consists of following problems: the Shanghai Cooperation Organization and the security problems in Central Asia, The strengthening security as the main part of the SCO activities, and the development of other spheres of cooperation such as energy security. The results of the SCO summit in Dushanbe. The NATO activities in the sphere of promoting security in the Central Asian region within the Partnership for Peace program. Cooperation algorithms between the NATO and other regional institutions. The SCO activities are directed to the promoting of the regional security in the region, paying key attention to international terrorism, religious extremism, illegal drug trafficking, organized crime and cyber crime as well as other threats which have trans bored character. It is also important to analyze the SCO member-states cooperation in the field of combating international terrorism and opium economy in Afghanistan as the main direction in promoting peaceful and prosperous development of the region. It is obvious that the solution of the above-mentioned problems is the common and collective task for the whole international community.